Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae) - Zhang, Yu-Qing; Li, Li-Zhen; Yin, Zi-Wei (Zootaxa, 2019)
The diversity of the ‘Pselaphodes complex’ of genera from Asia remains fragmentally documented. Herein we describe fifteen new species of the genus Labomimus Sharp from China: L. assingi sp. nov. and L. dilatatus sp. nov. from Shaanxi, L. longnan sp. nov. and L. minshanus sp. nov. from Gansu, L. chouwenii sp. nov. from Taiwan, L. yue sp. nov. from Guangdong, L. howaichuni sp. nov. from Hong Kong, L. jinfomontis sp. nov. from Chongqing, L. niger sp. nov. from Sichuan, L. maolan sp. nov. from Guizhou, L. corpulentus sp. nov., L. dulongensis sp. nov., and L. wuchaoi sp. nov. from Yunnan, and L. medogensis sp. nov. and L. qiujianyuae sp. nov. from Xizang. A little known species, L. torticornis (Champion), originally described from Assam, northeastern India, is newly recorded in Yunnan, southwestern China. Illustrations of the habitus and major diagnostic characters of all treated species are provided. A checklist and a distributional map of world species are given.